Diversity and population structure of Dipterocarpaceae species in Weh Island Nature Tourism Park, Indonesia - RIDHA UL FAHMI; SAIDA RASNOVI; ESSY HARNELLY (Jurnal Natural, 2021)
The Dipterocarpaceae family is one of the identified plant groups with high conservation value that exist in Weh Island Nature Tourism Park. However, the data availability on the species diversity and population structure of Dipterocarpaceae in Weh island in particular and Aceh in general is still very limited. Thus, it is necessary to conduct studies on species diversity and population structure of Dipterocarpaceae from Weh Island. This study aims to obtain data on species abundance and diversity, species composition of each stratum, population structure, and stand structure of Dipterocarpaceae in Weh Island Nature Tourism Park. This research utilized transect method with randomly selected plots according to topographic conditions. We found two Dipterocarpaceae species: Shorea sumatrana (Slooten) Desch and Dipterocarpus hasseltii Blume. Shorea sumatrana (Slooten) Desch has the greatest abundance of all types and strata. The diversity of Dipterocarpaceae species in Weh Island Nature Tourism Park is categorized as low because the diversity index value is in the range of H'1. This means that the presence of seedling and sapling strata from each species has a major effect on the survival of the Dipterocarpaceae family in the future. The stand structure of the Dipterocarpaceae family in normal conditions is indicated by an inverted “J” shaped diagram.